Investigating EFL Students’ Language Politeness in Their English-Speaking Practices: A Study on Grade X Students of SMA 1 Parangloe Gowa District - Nurfathana Mazhud; Ihramsari Akidah (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
The importance of language politeness is not just refining words, but conveying things that honestly reflect the pattern of civilized society. Language politeness is a very important aspect in shaping students' language and character. Assessment of language politeness is the ability of children to speak and with whom they speak. Speaking skills in students' language politeness can be seen when they communicate daily in both formal and non-formal environments. The age of children at the high school level is a period when thinking is full of idealism, so that this period requires personality formation to achieve positive behavior change, one of which is good communication behavior in the surrounding environment. Therefore, research on speaking skills in fostering language politeness among class X SMA Negeri 1 Parangloe becomes very meaningful for saving, habituation, and developing character values in realizing a civilized nation. This study aims to determine the language politeness of class X students of Sma Negeri 1 Parangloe during their learning interactions in class. The data analysis technique used with a qualitative approach is literature study to analyze the results of the student's conversation transcription in the learning process. Based on the results of research and discussion, it can be concluded that 1) The learning process at SMA Negeri 1 Parangloe, in general, students have high self-confidence to speak in public so that vocabulary is needed to be balanced with language politeness. 2) The most typical form of language behavior occurs during face-to-face conversations between people who come from the same culture so that the principles of politeness are applied in the learning process.